2009
DOI: 10.2109/jcersj2.117.359
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of complex sulfides AgCuS and Ag3CuS2 from the elements under hydrothermal conditions

Abstract: The hydrothermal technique was applied to the syntheses of ternary metal sulfides, AgCuS and Ag3CuS2, using silver, copper, and sulfur powders as starting materials. AgCuS was obtained as a single phase when the starting ratio of Ag:Cu:S was 0.9:1.1:1 in water above 120°C for 10 h except for synthesis condition at 120°C for 60 h and inductively coupled plasma (ICP) analysis revealed that experimental silver and copper contents in products were Ag0.89Cu1.10S. At 120°C for 60 h, some unidentified peaks were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition to this theoretical work, experimental work was carried out to synthesise and characterise both compounds, and to verify some of the theoretical predictions above. Both compounds were synthesised from a mixture of their constituent elements: AgCuS was obtained using a hydrothermal method similar to that used by Tokuhara et al , 59 while Ag 3 CuS 2 used a typical high temperature synthesis from the elements. In both cases, the products were obtained as black powders, and identified using powder X-ray diffraction; the resulting patterns were indexed in previously obtained space groups of Cmc 2 1 for AgCuS and I 4 1 / amd for Ag 3 CuS 2 , 33 , 34 and are shown in comparison to patterns simulated from those previous structures in ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this theoretical work, experimental work was carried out to synthesise and characterise both compounds, and to verify some of the theoretical predictions above. Both compounds were synthesised from a mixture of their constituent elements: AgCuS was obtained using a hydrothermal method similar to that used by Tokuhara et al , 59 while Ag 3 CuS 2 used a typical high temperature synthesis from the elements. In both cases, the products were obtained as black powders, and identified using powder X-ray diffraction; the resulting patterns were indexed in previously obtained space groups of Cmc 2 1 for AgCuS and I 4 1 / amd for Ag 3 CuS 2 , 33 , 34 and are shown in comparison to patterns simulated from those previous structures in ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AgCuS was synthesised using the hydrothermal method proposed by Tokuhara et al 59 Non-stoichiometric quantities of Ag (1.4314 g, 0.0133 mol), Cu (1.0306 g, 0.0162 mol), and S (0.4727 g, 0.0147 mol), using a molar ratio of 0.9 : 1.1 : 1.0, were ground together in an agate pestle and mortar. Of this mixture 0.5 g was transferred to a Teflon-lined steel autoclave (45 mL) together with 15 mL distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, we have studied a simple hydrothermal reaction using only an elemental metal and an elemental chalcogen as starting materials. In this manner, we have succeeded in synthesizing the binary metal sulfides of CuS [17,18], Cu 2 S [18], Ag 2 S [18], NiS [19], Co 9 S 8 [19], Ni 3 S 2 [19], ZnS [20], and CdS [20], and the complex ternary metal sulfides of Ag 3 CuS 2 [21] and AgCuS [21]. Among these sulfides, we have observed interesting particle shapes, such as polyhedral CuS and Cu 2 S. We considered whether this simple approach can possibly be applied to the synthesis of Bi 2 X 3 (X = S, Se, Te).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that pure CuS is obtained easily at low temperature, 60°C. 4),5) Silver sulfide (Ag 2 S), 5) iron sulfide (FeS), 6) cobalt sulfide (Co 9 S 8 ), 6) nickel sulfides (NiS, Ni 3 S 2 ), 6) and complex sulfides AgCuS 7) and Ag 3 CuS 2 7) can also be prepared under similar conditions.…”
Section: Introductionmentioning
confidence: 99%